Curriculum by competences: contextualized response for the educational attention of cultural diversity - Ramos-Hernández, Rosa R. (2022)
This article arises from the academic meeting of the doctoral seminar Development of Competences Through Didactic Planning of the Doctorate in Education Sciences of the Metropolitan University of Education, Science and Technology (UMECIT) is a reflective analysis on the challenge that intercultural education represents in the real and current contexts imposed by cultural mobility and its articulation with competencies in curriculum development; The purpose is to visualize the interrelationships of the migratory phenomenon in educational systems, from the necessary contextualization of the curriculum to cultural diversity. As a methodological support, critical reflection about the subject is carried out, from a qualitative analysis based on bibliographic or documentary sources, among its findings, it stands out that teachers need to appropriate a variety of pedagogical strategies that guide the teaching-learning processes, as a way of guarantee opportunities and achieve an approach to equity in the face of a globalized society. Likewise, that educational programs must reflect curricular proposals that guarantee the integral formation of the student, from an education focused on cultural valuation, in correspondence with the development of competencies focused on the effective attention of cultural diversity, beyond the simple admission of students of foreign origin to the educational system.